A New Approach to Fuzzy Metric Spaces and Their Similarity-Based Construction. (26th May 2016) - Soylu, Gültekin; Güloğlu, Mutlu
Abstract : We introduce a space of functions which can be interpreted as a similarity-based approach to fuzzy metric spaces. The triangle inequality we propose is defined by means of a fuzzy ordering. We compare the introduced space with fuzzy metric spaces in the sense of Seikkala and Kaleva. Finally we complete the work discovering the corresponding classical as well as fuzzy topologies.